Rancang Bangun Sistem Kontrol pH Air Pada Palka Ikan Muatan Hidup Menggunakan Mikrokontroler dan LabVIEW - Manalu, Trimas; Prayetno, Eko; Pramana, Rozeff; Nugraha, Sapta (Fakultas Teknik Universitas Maritim Raja Ali Haji, 2018)
The live fish storege currently is not able to control the pH parameters of the water according to the fishs living environment. pH needs to be considered so that fish can survive. The purpose of this research is to design a system that can control the pH of water in fish hatch using a microcontroller and LabVIEW. The test is carried out on the hatch with dimensions of 90 cm x 65 cm x 50 cm. Monitoring changes in pH values in real time is done through LCD and LabVIEW. This device is equipped with an LED indicator that can indicate the condition of the relay outside of the LaBVIEW software. The difference in sensor readings designed with a standard measuring instrument is only around 0.05. The appearance process of the sensor reading value on the LCD and LabVIEW runs well with a response time reading of about 0.5 seconds and with a response time in controlling the relay about 0.3 seconds. Fish can survive using a control system designed during the testing process within 2x24 hours. The reading value from the sensor will be stored in real time as long as the LabVIEW software runs.